2020
DOI: 10.1007/s00572-020-00979-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and phenology of fine root endophyte colonization across populations of Lycopodiella inundata

Abstract: Mycorrhizal fungi are critical components of terrestrial habitats and agroecosystems. Recently, Mucoromycotina fine root endophyte fungi (MucFRE) were found to engage in nutritional mutualism with Lycopodiella inundata, which belongs to one of the earliest vascular plant lineages known to associate with MucFRE. The extent to which this mutualism plays a role in resilient plant populations can only be understood by examining its occurrence rate and phenological patterns. To test for prevalence and seasonality i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…We chose to standardise our sampling to avoid any phenology bias among samples. A recent study on an early-divergent moss (Lycopodiella inundata) found that root colonisation by FRE was greater in autumn than in spring and authors attributed this to changes in temperature and rainfall (Kowal et al 2020). This further supports our results that FRE proliferate in wetter environments, but contradicts our results in regards to temperature.…”
Section: Ecological Drivers Of Fre and Amfsupporting
confidence: 66%
See 2 more Smart Citations
“…We chose to standardise our sampling to avoid any phenology bias among samples. A recent study on an early-divergent moss (Lycopodiella inundata) found that root colonisation by FRE was greater in autumn than in spring and authors attributed this to changes in temperature and rainfall (Kowal et al 2020). This further supports our results that FRE proliferate in wetter environments, but contradicts our results in regards to temperature.…”
Section: Ecological Drivers Of Fre and Amfsupporting
confidence: 66%
“…This further supports our results that FRE proliferate in wetter environments, but contradicts our results in regards to temperature. This is likely due to the fact the temperature range used by Kowal et al (2020) was 6 to 11 °C in spring and ~3 to ~16 °C in autumn; while ours was -1 to 9.9 °C. It is possible that colonisation by FRE follows a hump-shaped patter with temperature.…”
Section: Ecological Drivers Of Fre and Amfmentioning
confidence: 65%
See 1 more Smart Citation
“…in dual symbiosis (Field et al 2016, Rimington et al 2020. This situation parallels that in hornworts (Desirò et al 2013) and pteridophytes (Rimington et al 2015, with the only currently known exception being the lycophyte Lycopodiella inundata (L.) Holub which, after detailed sampling of several populations, appears to form partnerships, like Treubia and Haplomitrium, only with Mucoromycotina (Rimington et al 2015, Kowal et al 2020.…”
Section: Figurementioning
confidence: 62%
“…Trypan blue stains AM fungal vesicles and spores in a similar manner, making distinguishing these difficult and risking inflated quantification of mycorrhizal associations. Sheaffer blue ink represents a non-carcinogenic alternative stain for mycorrhizal structures [7–11]. A review of staining protocols by Moukarzel et al .…”
Section: Introductionmentioning
confidence: 99%